PENGEMBANGAN MEDIA PEMBELAJARAN POP-UP PENDIDIKAN KEWARGANEGARAAN SD/MI KELAS VI UNTUK MENINGKATKAN KREATIVITAS MAHASISWA PGMI UNISKA MAB BANJARMASIN - Desy Anindia Rosyida; Barsihanor Barsihanor (Program Studi PGMI STAI Al Falah Banjarbaru, 2019)
Learning about Citizenship Education (PKn) in general is a lecture, discussion and question, and answer. This will make students bored. Therefore, new innovations in the teaching and learning process, especially the Civics Education (PKn) course, are needed through the development of class I SD / MI Civics learning media with pop-ups. Because PGMI students are prospective educators, later they will teach general science and provide good examples to students. They will also be able to develop pop-up learning media in other learning materials. The first problem formulation, the absence of pop-up PKn SD / MI learning media that can be used as a reference for PKn teaching and learning process, and second, whether PKn pop-up learning media SD / MI class VI can improve the creativity of PGMI students Uniska MAB Banjarmasin. The research used is product and development (Research and Development). The assessment of design experts and material experts obtained an average value of 80%, 85% field testing stage, and the results of product trials on the activeness of students in the control class obtained values of 66, 75 and the Experimental class obtained a value of 77, 95. Keywords: Development, Pop-up Learning Media, Creativity